2022
DOI: 10.1098/rstb.2021.0282
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision in thrips (Thysanoptera)

Abstract: Insects are an astonishingly successful and diverse group, occupying the gamut of habitats and lifestyle niches. They represent the vast majority of described species and total terrestrial animal biomass on the planet. Their success is in part owed to their sophisticated visual systems, including colour vision, which drive a variety of complex behaviours. However, the majority of research on insect vision has focused on only a few model organisms including flies, honeybees and butterflies. Especially understud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…[101]), and preference for light of long wavelengths is found in many herbivorous pest insects, which either feed or oviposit on green leaves [102,103]. López Reyes et al [62] review what is presently known for thrips (the insect order Thysanoptera), and Döring & Kirchner [104] provide a model explaining the choice of aphids (Hemiptera) for substrates appearing green or yellow to the human eye.…”
Section: Diversity Of Colour-guided Behaviour and Colour Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…[101]), and preference for light of long wavelengths is found in many herbivorous pest insects, which either feed or oviposit on green leaves [102,103]. López Reyes et al [62] review what is presently known for thrips (the insect order Thysanoptera), and Döring & Kirchner [104] provide a model explaining the choice of aphids (Hemiptera) for substrates appearing green or yellow to the human eye.…”
Section: Diversity Of Colour-guided Behaviour and Colour Ecologymentioning
confidence: 99%
“…stomatopods: [61]; reviewed by [20]), where some of them influence spectral sensitivity. By contrast, López Reyes et al [62] report that the function of fluorescing filters observed in thysanopteran insects (thrips) still awaits understanding. Filter pigments can also be placed more proximally in the light path, affecting only part of the photoreceptors.…”
Section: Diversity Of Optical Mechanisms Tuning the Spectral Sensitiv...mentioning
confidence: 99%
“…Monitoring for WFT by its attraction to coloured sticky traps, in conjunction with chemical lures, capitalises on a natural behavioural response to colour while searching for potential host plants 1 . The WFT is known to show preferences to specific colours indicating colour discrimination capabilities, having a high response to blue and yellow and sometimes to UV-A light 2 . From the few electroretinogram (ERG) studies that have been conducted on WFT eyes, sensitivity peaks are found at ~ 360–365 (UV-A light) 3 , and at ~ 500–540 nm (green light) 3 , 4 , which is consistent with the presence of UV-A and green photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural studies also suggest that a blue photoreceptor is present 5 , which would increase the number of colours WFT is able to perceive and discriminate. However, there is ongoing debate regarding the most attractive colour to optimize WFT catches, especially between blue and yellow 2 , 6 . To date, much of the research on WFT trapping is based on measuring the number of landings on a target 2 , 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation